Uncovering obsessive-compulsive disorder risk genes in a pediatric cohort by high-resolution analysis of copy number variation. Issue 1 (December 2016) - Gazzellone, Matthew; Zarrei, Mehdi; Burton, Christie; Walker, Susan; Uddin, Mohammed; Shaheen, S.; Coste, Julie; Rajendram, Rageen; Schachter, Reva; Colasanto, Marlena; Hanna, Gregory; Rosenberg, David; et al.
Abstract Background Obsessive-compulsive disorder (OCD) is a heterogeneous neuropsychiatric condition, thought to have a significant genetic component. When onset occurs in childhood, affected individuals generally exhibit different characteristics from adult-onset OCD, including higher prevalence in males and increased heritability. Since neuropsychiatric conditions are associated with copy number variations (CNVs), we considered their potential role in the etiology of OCD. Methods We genotyped 307 unrelated pediatric probands with idiopathic OCD (including 174 that were part of complete parent-child trios) and compared their genotypes with those of 3861 population controls, to identify rare CNVs (<0.5 % frequency) of at least 15 kb in size that might contribute to OCD. Results We uncovered de novo CNVs in 4/174 probands (2.3 %). Our case cohort was enriched for CNVs in genes that encode targets of the fragile X mental retardation protein (nominalp = 1.85 × 10−03 ; FDR=0.09), similar to previous findings in autism and schizophrenia. These results also identified deletions or duplications of exons in genes involved in neuronal migration (ASTN2 ), synapse formation (NLGN1 andPTPRD ), and postsynaptic scaffolding (DLGAP1 andDLGAP2 ), which may be relevant to the pathogenesis of OCD. Four cases had CNVs involving known genomic disorder loci (1q21.1-21.2, 15q11.2-q13.1, 16p13.11, and 17p12). Further, we identifiedBTBD9 as a candidate gene for OCD. We also sequenced exomes of ten "CNV positive" trios and identified in one an additional plausibly relevant mutation: a 13 bp exonic deletion inDRD4 . Conclusions Our findings suggest that rare CNVs may contribute to the etiology of OCD.